System Design and Performance Evaluation of Wastewater Treatment Plants Coupled With Hydrothermal Liquefaction and Gasification - Amoedo, Rafael C.; Damartzis, Theodoros; Granacher, Julia; Marechal, Francois M. (Frontiers in Energy Research, 2020)
Wastewater treatment and sludge disposal are responsible for considerable costs and emissions in a global scale. With population and urbanization growing, tackling the rational and efficient use of energy while fulfilling the desired effluent standards are imperative. In this work, a superstructure-based approach is designed to incorporate alternative treatments for wastewater. In particular, technologies like hydrothermal liquefaction and gasification, coupled with technologies for CO2 conversion to value-added products are studied. Multi-objective optimization is applied as a way to generate multiple solutions that correspond to different system configurations. From a reference treatment cost of almost 0.16 $/mWW3, an environmental impact of 0.5kgCO2/mWW3 and an energy efficiency of 5%, different configurations are able to transform a waste water treatment plant to a net profit unit, with a net environmental benefit and energy efficiency close to 65%. The investment in hydrothermal liquefaction producing biocrude coupled with catalytic hydrothermal gasification demonstrated to yield consistently better total costs and environmental impacts. Parametric analysis is performed in the inlet flow of wastewater to account for different sizes of waste water treatment plant, with smaller inlets achieving values closer to those of the state-of-the-art configuration.